ANALISIS PENGARUH CELERITY ENDORSER DAN PROMOSI ONLINE TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE SHOP (STUDI KASUS PADA MAHASISWA UNIVERSITAS ISLAM MALANG DALAM GRUP WHATSAPP (TEMAN PENELITIAN SAYA) YANG MELAKUKAN BELANJA ONLINE DI MEDIA SOSIAL INSTAGRAM (@NATUREREPUBLIC.ID) - dina islamiyah; rini rahayu kurniati; dadang krisdianto (JIAGABI (Jurnal Ilmu Administrasi Niaga/Bisnis), 2020)
The purpose of this study is to determine how much influence the celebrity endorser and online promotion on purchasing decisions at the Nature Republic online shop either partially, simultaneously and dominantly. The method used is a quantitative method with a sample of 59 respondents. Data collection techniques were carried out using a questionnaire. Data analysis was performed by multiple linear regression analysis, t test, F test and coefficient of determination with the help of SPSS V25 data analysis program.